In a Genomic Era, Placental Pathology Still Holds the Key in the Nondysmorphic Stillbirth. (May 2018) - Campbell, Jamie; Armstrong, Kristy; Palaniappan, Nithiya; Maher, Eddy; Glancy, Mary; Porteous, Mary; Mckenzie, Kathryn J; Evans, Margaret J
Objective: To explore the relative utility of genetic testing in contrast to placental pathology in explaining causation of death in the structurally normal stillborn population. Methods: A retrospective review of a structurally normal stillborn infant cohort in South East Scotland between 2011 and 2015, defined by death at or after 24 weeks of gestation. We reviewed pathology reports and collected demographic data on cases. This information was collated with genetic test results (quantitative fluorescent polymerase chain reaction and microarray analysis) and placental pathology to create a database for analysis. Primary Results: Within the structurally normal population (n = 131), there were 125 genetic tests performed and 11 abnormal results. Sixty-six microarray analyses were performed, and 2 (3%) of the results were thought likely to reflect cause of stillbirth (1 case of incomplete trisomy 4 and 1 case of deletion of chromosome Xp in a female). Analysis was significantly limited in 2 cases as parental samples were not available. The placental pathology was available in a total of 129 cases; significant findings were identified in 100 cases; 79 (61%) showed changes that were considered to have caused death (including cord "accidents"), and a further 21 (16%) showed findings likely to influence the management of subsequent pregnancies. Conclusions: We reaffirm the utility of placental examination in the investigation of stillbirth. In cases of nondysmorphic stillbirth where placental pathology does not explain the cause of stillbirth, microarray analysis of fetal DNA can add further diagnostic information in 3% of cases but can add further diagnostic confusion, and it is important that parental bloods are taken to minimize this risk.